Dzielić się mądrością czasu w rodzinie. Wyzwania etyczne współczesnych przemian demograficznych w Polsce - Kućko, Wojciech (Teologia i Moralność, 2020)
One of the major challenges facing European societies is the issue of aging populations. This implies not only questions about the demographic future of states and nations but also provokes reflection on ethical issues related to old age. The article is an attempt to show what new ethical dilemmas related to demographic processes Polish society faces. An important point of reference may be the principles of Catholic ethics, especially solidarity between generations, i.e. sharing the wisdom of time and treating the elderly as an opportunity for young people. This issue is pointed out by Pope Francis.